2013
DOI: 10.1177/0265659013492784
|View full text |Cite
|
Sign up to set email alerts
|

The New Reynell Developmental Language Scales: Descriptive account and illustrative case study

Abstract: This article describes the development of new scales for assessing the status of a young child’s language comprehension and production. Items and sections on the scales were included to reflect advances in research on language acquisition and impairment. The New Reynell Developmental Language Scales (NRDLS) were trialled on 301 children and then standardized on a sample of 1,266 participants across the age range 2;00–7;06 years. Evaluations of reliability (internal and test–retest) and concurrent validity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Unknown ratings of evidence were applied to both the internal consistency of the NRSLD (Letts et al 2014) and inter-rater reliability assessments of the BSID-III (Moore et al 2012). Whilst both results met Terwee criteria, the methodological quality of the studies were poor rendering the findings inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…Unknown ratings of evidence were applied to both the internal consistency of the NRSLD (Letts et al 2014) and inter-rater reliability assessments of the BSID-III (Moore et al 2012). Whilst both results met Terwee criteria, the methodological quality of the studies were poor rendering the findings inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…The Leiter-R is an objective nonverbal test of cognitive abilities that has been used for testing children with autism (Grondhuis & Mulick, 2013; Shah & Holmes, 1985; Tsatsanis et al, 2003). The Reynell Developmental Language Scales is another objective test designed to evaluate both expressive and receptive language in young children, including those with autism (Kaale, Fagerland, Martinsen, & Smith, 2014; Kjellmer et al, 2012; Reynell & Gruber, 1990). This test has revealed language comprehension delays, along with a high level of variability in the development of language comprehension in children with autism (Kjellmer et al, 2012; Reynell & Gruber, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…The Reynell Developmental Language Scales is another objective test designed to evaluate both expressive and receptive language in young children, including those with autism (Kaale, Fagerland, Martinsen, & Smith, 2014; Kjellmer et al, 2012; Reynell & Gruber, 1990). This test has revealed language comprehension delays, along with a high level of variability in the development of language comprehension in children with autism (Kjellmer et al, 2012; Reynell & Gruber, 1990). The Reynell test sessions were video recorded and we subsequently scored the performance of the children using both the testing session and the digitized files.…”
Section: Methodsmentioning
confidence: 99%
“…Only three published articles by authors of assessments were identified. One of these contained information on the development, standardization and psychometric properties of the NRDLS (Letts et al, 2014 ). This study was not included in this review as it was published after the assessment manual and contained no new information.…”
Section: Resultsmentioning
confidence: 99%